STRATEGI POLA KOMUNIKASI DALAM PEMBENTUKAN DISIPLIN HAFALAN AL-QUR'AN PADA ANAK ASUH - Nur Rahman, Wildian Fajrin; Hady, Yazid; Hermansah, Tantan; Fanshoby, M.; Ismail, Muhammad (Center for Gender and Child Studies (Pusat Studi Gender dan Anak) LP2M UIN Syarif Hidayatullah Jakarta, 2024)
Abstract. This study investigates the communication patterns used by caregivers at Pondok Yatim and Dhu'afa Amal Sholeh Sejahtera Foundation, a non-profit organization focused on religious social outreach, to cultivate discipline in foster children's Qur'an memorization. Using Josep A. Devito's communication pattern theory, this research examines the effectiveness and challenges of various communication models in this context. Employing a qualitative, descriptive approach, data were gathered through direct observation, interviews, and documentation. Results reveal that caregivers predominantly use the